1995
DOI: 10.1097/00000539-199511000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Ropivacaine Infusion for Postoperative Analgesia After Major Lower Abdominal Surgery--A Dose Finding Study

Abstract: Ropivacaine exhibits less cardiotoxicity and causes less motor block than bupivacaine when used in equianalgesic doses. This makes ropivacaine potentially well suited for epidural infusion for postoperative analgesia. The aim of this study was to determine which of three concentrations of epidurally administered ropivacaine infused for postoperative analgesia would attenuate intravenous opioid analgesia requirements while also minimizing motor block. Forty ASA I-III patients, having major lower abdominal surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 3 publications
1
27
0
2
Order By: Relevance
“…First, we could have confined the catheter insertion site to thoracic levels (based on the considerations above), or second we could have used lower doses of local anaesthetics. However, the latter might have led to insufficient analgesia [13]. Since we were already using a reasonably low dose of ropivacaine with an opioid, which has been recommended as an effective postoperative analgesic after abdominal surgery [13][14][15], we chose not to reduce local anaesthetic concentrations further but instead change the insertion sites to thoracic level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we could have confined the catheter insertion site to thoracic levels (based on the considerations above), or second we could have used lower doses of local anaesthetics. However, the latter might have led to insufficient analgesia [13]. Since we were already using a reasonably low dose of ropivacaine with an opioid, which has been recommended as an effective postoperative analgesic after abdominal surgery [13][14][15], we chose not to reduce local anaesthetic concentrations further but instead change the insertion sites to thoracic level.…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter might have led to insufficient analgesia [13]. Since we were already using a reasonably low dose of ropivacaine with an opioid, which has been recommended as an effective postoperative analgesic after abdominal surgery [13][14][15], we chose not to reduce local anaesthetic concentrations further but instead change the insertion sites to thoracic level. Our results suggest that thoracic epidural analgesia was as successful as lumbar epidural analgesia [9,16].…”
Section: Discussionmentioning
confidence: 99%
“…HORACIC epidural analgesia (TEA) is an effective technique to reduce postoperative pain in patients undergoing major abdominal surgery. [1][2][3][4] However, the results of the intraoperative use of TEA in combination with general anesthesia are still controversial with respect to a reduction of postoperative pain perception or postoperative analgesic consumption. [5][6][7][8][9][10] This can be explained in part by the variety of types and sites of surgery, 11 or by the presence or absence of pain before surgery.…”
Section: Me Et Th Ho Od Ds S:mentioning
confidence: 99%
“…The optimal concentration of ropivacaine has been suggested as 2 mg/mL (0.2%) when used for epidural analgesia [2,8,9]; however, this concentration was shown to lead to excessive motor blockade and urinary retention [1,10]. Lower concentrations of ropivacaine can be helpful in minimizing motor blockade and other side effects since the concentration of local anesthetic solution is a major determinant of motor blockade with PCEA [2].…”
Section: Discussionmentioning
confidence: 99%
“…Lower concentration of local anesthetic can be used for epidural analgesia to minimize motor blockade of the lower limbs. Scott et al reported that there was a dose-related increase in the amount of motor blockade [9]. Approximately 30% of patients with an epidural infusion of 0.2% ropivacaine demonstrated motor blockade of the lower limbs, but the incidence of motor blockade was very low in an epidural infusion of ropivacaine 0.1%.…”
Section: Discussionmentioning
confidence: 99%